Investigation of the inter-rater reliability of three different plaque indices used in patients with fixed orthodontic appliances - Christina Erbe; Teresa Temming; Daniela Ohlendorf; Irene Schmidtmann; Priscila Ferrari-Peron; Ambili Mundethu; Heinrich Wehrbein (PLoS ONE, 2025)
Background/Objectives To analyze the inter-rater reliability of three different plaque indices with regard to raters’ orthodontic experience. Materials/Methods The study analyzed 50 photographs of patients with maxillary and mandibular multibracket appliances (MB), captured via Digital Plaque Imaging Analysis (DPIA) for plaque assessment. Three indices - the modified Turesky index (TQH index), Attin index, and modified bonded bracket index (mBB index) were used. Fourteen evaluators with varying orthodontic experience levels (four with limited, five with moderate, and five with extensive experience) assessed the images. Results The highest agreement among the evaluators in terms of ICC was obtained using the Attin index and the mBB index. The TQH index yielded the poorest agreement among evaluators. Orthodontic experience had no significant effect on inter-rater reliability. The evaluators with little orthodontic experience scored best in agreement with the Attin index, and the evaluators with much orthodontic experience scored best with the Attin and mBB indices. No difference was observed between the three plaque indices among the evaluators with moderate orthodontic experience. Limitations Consistent classification of subjects into the same oral hygiene category by multiple raters using a plaque index was difficult. Consequently, calibration of raters in practice may lead to a more unanimous classification of patients into the same oral hygiene category. A disadvantage of the classification of plaque values into oral hygiene categories was posed by the category boundaries. These resulted in two plaque indices being less consistent than was the case in reality. Conclusions/Implications We recommend the use of an orthodontic plaque index (Attin index) or a combined dental and orthodontic plaque index (mBB index) in patients with an MB. The TQH index, considered the international standard plaque index, is less appropriate for application in these patients. Training and calibration of evaluators are of great importance when applying conventional plaque indices.